Detection of Factor XIII deficiency: data from multicentre exercises amongst UK NEQAS and PRO‐RBDD project laboratories. (13th April 2017) - Jennings, I.; Kitchen, S.; Menegatti, M.; Palla, R.; Walker, I.; Makris, M.; Peyvandi, F.
Summary: Introduction: FXIII deficiency is a rare bleeding disorders, and specific FXIII assays are recommended to detect this deficiency. We investigated the performance and accuracy of FXIII investigations in two exercises, comparing centres enrolled in the PRO‐RBDD project (prospective data collection on patients with fibrinogen and Factor XIII deficiencies), and UK NEQAS BC centres. Methods: Samples from a FXIII deficient subject and a normal donor were sent to participating centres, to investigate for FXIII deficiency, and interpret their results. Median, coefficient of variation and range were determined. Results: Results were returned from 98 UK NEQAS BC and 28 PRO‐RBDD centres. Up to 40% of UK NEQAS BC and 52% of PRO‐RBDD centres reported clot solubility results – with diagnostic errors by two NEQAS BC centres (false negatives for the FXIII deficient sample) and one PRO‐RBDD centre (false positive for the normal sample). Over 70% of UK NEQAS BC centres and PRO‐RBDD centres performed FXIII assays. Median results were similar between the two groups, with the exception of sample 3 in survey 2 (5.5 vs . 14.0 μ/dl for UK NEQAS BC and PRO‐RBDD centres respectively, P < 0.001). Diagnostic errors were made by 2 UK NEQAS BC centres. Conclusion: Approximately 70% of centres now employ FXIII assays, complying with international recommendations. However, solubility tests continue to be used. Our data show this can be successful, depending on the sensitivity of the method in use. Diagnostic errors are made by centres using both solubility screens and FXIII assays, and laboratories should ensure good quality assurance procedures to improve diagnostic accuracy.